2012
DOI: 10.3390/v4123689
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Alpaca Respiratory Coronavirus Most Closely Related to the Human Coronavirus 229E

Abstract: In 2007, a novel coronavirus associated with an acute respiratory disease in alpacas (Alpaca Coronavirus, ACoV) was isolated. Full-length genomic sequencing of the ACoV demonstrated the genome to be consistent with other Alphacoronaviruses. A putative additional open-reading frame was identified between the nucleocapsid gene and 3'UTR. The ACoV was genetically most similar to the common human coronavirus (HCoV) 229E with 92.2% nucleotide identity over the entire genome. A comparison of spike gene sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 34 publications
(39 reference statements)
0
68
0
2
Order By: Relevance
“…Conversely, clinical isolates display a full-length ORF4 sequence [32]. An intact ORF4 is also observed in bat and camel viruses related to HCoV-229E [19,22], whereas the alpaca alpha-CoV displays a onenucleotide insertion, resulting in a frameshift [20] ( Figure 1B). The availability of only a single alpaca CoV genome makes it impossible to determine whether the inserted sequence is representative of the alpaca CoV population or, else, if it represents a sequencing error.…”
Section: Hcov-oc43mentioning
confidence: 92%
See 2 more Smart Citations
“…Conversely, clinical isolates display a full-length ORF4 sequence [32]. An intact ORF4 is also observed in bat and camel viruses related to HCoV-229E [19,22], whereas the alpaca alpha-CoV displays a onenucleotide insertion, resulting in a frameshift [20] ( Figure 1B). The availability of only a single alpaca CoV genome makes it impossible to determine whether the inserted sequence is representative of the alpaca CoV population or, else, if it represents a sequencing error.…”
Section: Hcov-oc43mentioning
confidence: 92%
“…CoVs closely related to HCoV-229E were recently isolated from African hipposiderid bats [19], and a CoV belonging to the same species as HCoV-229E had been described in captive alpacas suffering from an acute respiratory syndrome [20,21] (Figure 1A). Analysis of these viral genomes indicated that, compared to HCoV-229E, they carry an additional ORF at the genomic 3' end [20] ( Figure 1B). This ORF, which is designated ORF8 but shares no Box…”
Section: Synonymous Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…The single virus strain, termed Alpaca coronavirus (ACoV), was fully sequenced and found to be highly related to known HCoV-229E strains. Epidemiological records suggested that the virus had caused a small outbreak of respiratory disease in exposed alpacas (Crossley et al, 2010(Crossley et al, , 2012, but it was never observed in feral animals. As no knowledge existed on related viruses other than HCoV-229E at that time, the finding was difficult to interpret as the strain could simply have been acquired from humans.…”
Section: Hcov-229ementioning
confidence: 99%
“…Also FIPVs seem to have lost the ability to replicate in the enteric tract (Pedersen, 2014). Clinical isolates of human coronavirus 229E as well as of the related alpaca coronavirus, both of which cause respiratory infections, encode relatively short spike proteins that lack the NTR (Crossley et al, 2012;Farsani et al, 2012). In contrast, closely related bat coronaviruses with intestinal tropism contain S proteins with a NTR or sometimes even two copies of the NTR (Corman et al, 2015) (Fig.…”
Section: S 1 Ntr Changesmentioning
confidence: 99%